0299 Sleep Loss Degeneration of Locus Coeruleus Neurons is Tau-Dependent. (27th April 2018) - Bell, P; Fenik, P; Brandes, M; Francois, N; Shulman, K; Zhu, Y; Veasey, S
Abstract: Introduction: Chronic short sleep (CSS), common in modern society, results in degeneration of Locus Coeruleus neuron (LCn). Recently we have identified increased concentrations of phosphorylated microtubule associated protein tau (p-tau). P-tau is implicated in degeneration of neurons in several conditions including Alzheimer's and Epilepsy. Here, we tested the hypothesis that tau contributes to the CSS-induced degeneration of LCn. Methods: We tested two conditions of tau knock down: transgenic knock out of tau protein and SiRNA knock down of tau protein via local injection. Tau -/- and wild type (WT) controls were randomized to CSS or Rested conditions. Following CSS, mice were perfused, and brains prepared for immunohistochemistry. Labeled LCn were stereotactically counted. In a second group of WT mice, mice were injected bilaterally into the LC nuclei with wither tau SiRNA or control (GFP) SiRNA. As above brains were procured for LCn counts. LCn were immunolabeled with anti-tyrosine hydroxylase (TH). Sections were mounted, dried, and counter-stained with Giemsa and confirmed to span rostral-caudal nucleus for each mouse. Neuronal counts were estimated using an optical fractionator minimally-biased approach. Results: While WT mice exposed to CSS produced the expected reduction in LCn counts by stereology (Bonferroni corrected t=3.7, p<0.01), Tau -/- mice conferred resistance to CSS LCn degeneration (t=0.0, N.S.). WT mice treated with tau SiRNA and exposed to CSS maintained normal LCn counts, whereas mice injected with GFP SiRNA showed significantly lower LCn counts (t=3.9, p<0.01), consistent with counts in WT mice exposed to CSS. Conclusion: These data support a role for tau in the CSS degeneration of LCn. Support (If Any): NIH grants R01 HL123331, HL 124576, and AG054104 to S.V.